GALON FISH SMART (GFS) : INOVASI KKN UNIVERSITAS PEKALONGAN KEMBANGKAN BUDIDAYA IKAN DALAM GALON DAN DIGITALISASI UMKM DI KELURAHAN NOYONTAANSARI - Putri Awaliya Rahmasari; Devin Agung Pramana; Ali Mustakim; Febianti Dwi Amalia; Kamilia Qothrunnada; Diva Febiyanti; Resviana Cahyawati; Kevin Kurniawan; Jamilatunni’mah Jamilatunni’mah; Hernawan Adi Saputra; Zaidan Permananda; Dian Milasari (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2026)
The problem of plastic waste and limited land in urban areas like Noyontaansari Village requires innovative solutions that integrate environmental and economic aspects. This community service program aims to transform community behavior in managing plastic waste through the Galon Fish Smart (GFS) innovation and improve living standards through digital entrepreneurship. The implementation method used includes three main stages: outreach, technical education, and hands-on practice in building aquaculture installations, as well as digital marketing assistance. The program results show that the community has successfully transformed used gallons into a multifunctional aquaponics system that combines fish farming with vegetable crops such as kale, shallots, and chilies. This innovation has proven effective in reducing household expenses and increasing food self-sufficiency. In addition, digitalization assistance helps local MSMEs expand their market reach through promotions on social media and managing marketplace accounts. Overall, the synergy between sustainable waste management and digital literacy has successfully created economic independence for the residents of Noyontaansari Village. Keywords: Smart Fish Gallon, Fish Cultivation, SME Digitalization, Plastic Waste, Food Security.